Toward Air Stability of Thin GaSe Devices: Avoiding Environmental and Laser‐Induced Degradation by Encapsulation. (9th October 2018) - Zhao, Qinghua; Frisenda, Riccardo; Gant, Patricia; Perez de Lara, David; Munuera, Carmen; Garcia‐Hernandez, Mar; Niu, Yue; Wang, Tao; Jie, Wanqi; Castellanos‐Gomez, Andres
Abstract: Gallium selenide (GaSe) is a novel 2D material, which belongs to the layered III–VIA semiconductors family and attracted interest recently as it displays single‐photon emitters at room temperature and strong optical nonlinearity. Nonetheless, few‐layer GaSe is not stable under ambient conditions and it tends to degrade over time. Here atomic force microscopy, Raman spectroscopy, and optoelectronic measurements are combined in photodetectors based on thin GaSe to study its long‐term stability. It is found that the GaSe flakes exposed to air tend to decompose forming first amorphous selenium and Ga2 Se3 and subsequently Ga2 O3 . While the first stage is accompanied by an increase in photocurrent, in the second stage, a decrease in photocurrent is observed, which leads to the final failure of GaSe photodetectors. Additionally, it is found that the encapsulation of the GaSe photodetectors with hexagonal boron nitride (h‐BN) can protect the GaSe from degradation and can help to achieve long‐term stability of the devices. Abstract : The degradation of thin GaSe in air is a complex process that involves photooxidation and generates various byproducts such as elemental selenium and Ga2 O3 . This degradation has profound influences on the optoelectronic properties of devices based on this layered material.